Comparing trauma exposure, mental health needs and service utilization across clinical samples of refugee, immigrant, and non-immigrant and U.S.-Origin Children - Betancourt, T.; Samson, Elizabeth; Birman, D.; Lee, R.; Ellis, H.; Layne, C. (Kluwer Academic/Plenum Publishers, 2017)
Most mental health services for trauma-exposed children and adolescents were not originally developed for refugees. Information is needed to help clinicians design services to address the consequences of trauma in refugee populations. We compared trauma exposure, psychological distress, and mental health service utilization among children and adolescents of refugee-origin, immigrant-origin, and U.S.-origin referred for assessment and treatment by U.S. providers in the National Child Traumatic Stress Network (NCTSN). We used propensity score matching to compare trauma profiles, mental health needs, and service use across three groups. Our sample comprised refugee-origin youth (n = 60, 48.3% female, mean age = 13.07 years) and propensity-matched samples of immigrant-origin youth (n = 143, 60.8% female, mean age = 13.26 years), and U.S.-origin youth (n = 140, 56.1% female, mean age = 12.11 years). On average, there were significantly more types of trauma exposure among refugee youth than either U.S.-origin youth (p < .001) or immigrant youth (p ≤ .001). Compared with U.S.-origin youth, refugee youth had higher rates of community violence exposure, dissociative symptoms, traumatic grief, somatization, and phobic disorder. In contrast, the refugee group had comparably lower rates of substance abuse and oppositional defiant disorder (ps ranging from .030 to < .001).This clinic-referred sample of refugee-origin youth presented with distinct patterns of trauma exposure, distress symptoms, and service needs that merit consideration in services planning.